Global, regional and national burden of asthma attributable to NO2 from 1990 to 2021: an analysis from the Global Burden of Disease Study 2021 - Chunyi Zhang; Jian Sun; Jingli Li; E Qin; Lingjing Liu; Guimei Pu (BMJ Open)
Objectives This study aims to systematically assess the global, regional, and national burden of asthma attributable to nitrogen dioxide (NO₂) pollution.Design and setting Analysis of population-level data from 1990 to 2021 obtained from the Global Burden of Disease Study 2021, covering 204 countries and territories.Participants Participants included patients with asthma attributable to NO₂ pollution.Main outcomes and measures Asthma-related disability-adjusted life-years (DALYs) and age-standardised DALY rates (ASDR) attributable to NO₂ pollution across 204 countries and territories. The estimated annual percentage change (EAPC) was used to assess temporal trends to identify regions with increasing or decreasing asthma burdens.Results In 2021, NO₂ pollution contributed to approximately 176.73 thousand DALYs globally, with an ASDR of 2.48 per 100 000 population (95% uncertainty interval (UI) −2.26 to 10.30). The global ASDR declined significantly from 1990 to 2021, with an EAPC of −1.93% (95% CI −2.14% to −1.72%). High-income North America had the highest ASDR (10.74 per 100 000; 95% UI 10.12 to 46.56), while Australasia experienced the most significant reduction in ASDR over the study period (EAPC −3.92%; 95% CI −4.46% to −3.37%). In contrast, Oceania and Southeast Asia showed increasing trends in asthma burden, with EAPCs of 2.33% (95% CI 1.57% to 3.10%) and 1.14% (95% CI 0.81% to 1.47%), respectively. The 5–9 age group carried the highest asthma burden, reflecting the vulnerability of younger children to NO₂ exposure. A positive correlation between ASDR and sociodemographic index (SDI) was observed (R=0.637, p<0.001), indicating a greater asthma burden in higher SDI regions.Conclusion The findings highlight significant regional and demographic disparities in asthma burden attributable to NO₂ pollution. Tailored public health strategies are needed to address the rising burden in vulnerable regions. Future research should focus on identifying effective interventions to reduce NO₂ exposure and improve asthma outcomes, especially in rapidly developing areas.